Addressing The Phenomenon Of Kinship Politics: An Experience Of The Prophetic Hadis - Sa'diyah, Fatichatus (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Indonesia is a democracy. The election of the government is also based on open, honest and fair elections. However, recent political conditions do not reflect Indonesiass status as a democracy. The purpose of this article is to explain the view of the Prophet’s hadis related to the phenomenon of kinship politics. This type of research is library research using qualitative data in the form of documentation and then analyzed with inductive analysis. In addition, the author also uses the hadis mawdu>`i> method, which collects traditions related to one topic or discussion, then arranges them based on their asba>b al-wuru>d and then provides an explanation based on the Prophetic tradition. In analyzing this problem, the author also uses conflict management theory. Based on the results, kinship politics is commonly known as nepotism. It can be seen that there are several Arabic words that are similar to the word ‘nepotism’ including; athara, `isa>bah. It is explained in the Prophet’s hadith that after the Prophet's death, there will be the phenomenon of atharah, which is nepotism. In the hadith, the Prophet also provided a solution when the phenomenn was encountered, namely being patient. Based on the theory of `asa>biyyah Ibn Khaldun states that the attitude of `asa>biyah can be interpreted in two senses; positive and negative. A positive attitude shows the concept of brotherhood, while a negative attitude shows blind fanaticism without seeing the truth.",